Intradermal eccrine poroma. Presentation of a case - Javier Martínez Navarro; Adialys Acosta Rodríguez; Martha Yudey Rodríguez del Pino; Virgen Yazmín Martínez Navarro (Medisur)
Eccrine poromas are benign adnexal tumors which originate from the intraepidermal duct portion of the sweat gland. They represent approximately 10% of all tumors of these glands. The classical variant of poroma is characterized by a neoformation of papular aspect of skin color or erythematous, with a predilection for palms and soles. However, these tumors in clinical terms may exhibit polymorphic characteristics that may make diagnosis difficult. In these cases, dermatoscopy is an immediate and useful tool that can support it. The histopathological study is necessary for the definitive conclusion. It is usually diagnosed between the fifth and seventh decades of life. For these reasons the case of a 30-year-old patient diagnosed with eccrine poroma in a palmar lesion is presented.